ICoFM2016-41: Catalyst-Free Growth of ZnO Nanowires on ITO Seed/Glass By Thermal Evaporation Method: Effects of ITO Seed Layer Thickness - Alsultany, Ferat H.; Hassan, Z.; Ahmed, Naser M. (2016)
Abctract: A seed lcatalyst-free growth of ZnO Nanowires (ZnO-NWs) on a glass substrate were succesfully fabricated using thermal evaporation technique. These Nanowires were grown on ITO seed layers of different thicknesses of 25 and 7S nm. which were depocited on glass substrates by radio frequency (RF) magnetron sputtering. Prior to synthesized ITO nanowires, the sputtered ITO seeds were annealed using the continuous wave (CW) C02 laser at 45O °C in air far I5 mins. The effect of seed layer thickness on the morphological structural and optical properties of ZnO-NWs were systematically investigated by X-ray diffraction (XRD), field emission Keywords: ZnO nanowires,annealing, ITO seed layer, Glass Substrate, Thermal evaporation CW CO2 laser